The Effectiveness of compassion focused therapy on developmental assets in adolescent with cancer - Fasih, ParastooSadat; Razeghi, Narges (International Journal of Applied Behavioral Sciences, 2021)
Background and Aim:The efficiency of The Compassion-Focused Therapy on development assets in adolescent with cancer were examined. Materials and Methods:The study was carried out as a quasi-experimental study with pretest/posttest design and a control group. The study population consisted of 30 teenagers at the age range of 12-18 years. They were selected through simple random sampling method and grouped in control and experimental groups. The experimental group attended eight training sessions (90min) of Compassion Focused Therapy. Data gathering tools were developmental assets scale Minnesota. Results:The MANCOVA showed that compassion-focused therapy had a positive and significant effect on more elements on developmental assets(P<0.01). So that there was a significant difference between the control and experiment groups in terms of the elements support, empowerment, constructive use of time, commitment to learning, positive values, social competencies, and positive identity (P<0.01). However, the difference was not significant with the expectations (P>0.05). Conclusion:The findings showed that CFT was effective in improving social relationships and acceptability by others through special concentration on awareness, expressing love, and kindness in teenagers with cancer.